A novel shaped ceramic-paraffin composite phase change energy storage material and preparation method thereof

The ceramic/paraffin composite phase change energy storage material with a pearl shell "brick-mud" structure imitated by magnetic field frozen casting and pressure-free impregnation technology was prepared, which solved the problems of low thermal conductivity and easy leakage of paraffin phase change energy storage materials, and achieved the effects of high thermal conductivity and high energy storage density. At the same time, the process was simple and environmentally friendly.

CN117447226BInactive Publication Date: 2025-04-11JILIN JIANZHU UNIVERSITY

Patent Information

Application Number
CN202311199531.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing paraffin phase change energy storage materials have low thermal conductivity and are prone to leakage during the phase change process, which affects their application efficiency and environmental friendliness.

Method used

Al2O3 and SiO2 porous ceramics with imitation of pearl shell "brick-mud" structures were prepared by magnetic field frozen casting and pressure-free impregnation technology, and paraffin was impregnated with pressure-free to form ceramic/paraffin composite phase change energy storage material.

Benefits of technology

It improves the thermal conductivity and energy storage density of composite materials, ensures that paraffin does not leak in ceramic carriers, improves energy storage efficiency, and is simple in process, low in cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117447226B_ABST
    Figure CN117447226B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a shaped pearl oyster-like structure ceramic-paraffin composite phase change energy storage material, which relates to the field of new material preparation, in order to overcome the problems of low thermal conductivity of phase change energy storage materials during phase change, easy leakage of phase change materials, complex preparation process and low efficiency. The raw materials of the shaped pearl oyster-like structure ceramic-paraffin composite phase change energy storage material are composed of Al2O3, Fe3O4 ceramic powder and industrial paraffin. The present invention adopts magnetic field freezing casting to prepare pearl oyster-like "brick-mud" Al2O3 porous ceramics, and obtains composite phase change energy storage materials after pressureless infiltration of paraffin in porous ceramics. The composite material has high energy storage density, high thermal conductivity, and controllable microstructure. After the paraffin is melted, it does not leak in the ceramic carrier, has high energy storage efficiency, and is environmentally friendly. By imitating the highly ordered "brick-mud" microstructure of pearl oysters to construct a continuous and orderly heat transfer path, the ceramic skeleton can achieve high thermal conductivity and anisotropy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new material preparation, and more specifically, to a pearl oyster-like "brick-mud" structured ceramic / paraffin composite phase-change energy storage material and a preparation method thereof. Background Art

[0002] The increasing energy consumption has become a major challenge for the development of human society, and improving energy efficiency is of great significance. Organic phase change energy storage materials such as paraffin can store and release a large amount of heat energy during the melting and solidification process. They have the advantages of high heat storage density, low cost, environmental friendliness, and good thermal stability. They have been widely studied in the fields of new energy development and utilization and medium and low temperature energy storage. The low thermal conductivity and easy leakage of paraffin during the phase change process seriously affect its practical application. The former makes the heat transfer speed of the application system slow and the heat storage efficiency low; the latter leads to a decrease in energy storage density and damages the environment. The researchers proposed that the composite preparation of shaped phase change materials by combining ceramics with paraffin can solve the above problems. Shape-fixed phase change materials refer to phase change materials that can maintain their original shape during the phase change process, can automatically absorb or release latent heat during the phase change process, can regulate the ambient temperature to achieve energy conservation and emission reduction, and have a wider application prospect. The Chinese patent application number 201510062562.3, publication number CN104645907A, and invention title "A method for preparing a heat-crosslinked nano paraffin phase-change energy storage capsule" uses a crosslinking method to obtain a nano paraffin phase-change energy storage capsule with a stable structure. Another example is the Chinese patent application number 202010861453.9, publication number CN111944494A, and invention title "A method for preparing expanded vermiculite-paraffin-PAM shaped phase-change energy storage material" that obtains a paraffin / PAM shaped phase-change material with high mechanical strength by emulsion polymerization. The microencapsulation method, blending method, and crosslinking method for encapsulating paraffin all have the disadvantages of poor encapsulation effect of phase change materials, complex processes, and low preparation efficiency.

[0003] In recent years, researchers have used the infiltration method to prepare shaped ceramic / phase change material composites, which have attracted people's attention. It will stably distribute liquid phase change materials in the pores of porous ceramics through capillary force. It not only combines the advantages of traditional phase change materials and the thermal properties of ceramics, but also is expected to solve the melting and leakage problem of phase change materials. For example, the Chinese patent publication number CN201710134385.4, published on August 14, 2017, the invention titled "A paraffin / iron tailings ceramic composite phase change energy storage material and its melt infiltration preparation method" prepares iron tailings porous ceramic carriers through foam injection molding-low temperature sintering process, and then prepares paraffin / iron tailings ceramic composite phase change energy storage materials through melt infiltration process. The melt infiltration of this liquid phase change material is particularly sensitive to the microstructure of the porous ceramic skeleton (such as pore morphology and size).

[0004] The currently developed freeze casting method (i.e., freeze drying method or ice template method) is a new preparation process for preparing porous materials. It can produce interconnected pores. By adjusting the freeze casting process, the pore morphology and size can be well controlled, and its scale can reach several microns to tens of microns. Therefore, some new structural composite materials can be prepared by combining the freeze casting method with the infiltration method. China Patent Publication No. CN201911078840.9, Publication Date February 4, 2020, the invention and creation name "a composite phase change material with PVA as a skeleton material and its preparation method" uses freeze drying to successfully prepare PVA aerogel as a skeleton material, and uses melt infiltration to load the phase change functional material onto the skeleton material. China Patent Application No. 202010357914.9, Publication No. CN111574137A, the invention and creation name "a shell-like pearl mother-of-pearl layer material with a layered structure and its preparation method" combines freeze casting technology with carbonization technology to obtain a layered shell-like pearl layer material with high fracture toughness and durability. The nacre of shells has a unique multi-scale "brick-mud" structure formed by the staggered arrangement of inorganic phases and organic matter, and exhibits excellent toughness despite the presence of highly brittle inorganic phases. Imitation of the highly ordered "brick-mud" microstructure of pearl oysters can construct a continuous and orderly heat transfer path, which is expected to solve the problem of low thermal conductivity of phase change materials. From the literature search, it is known that the current research on freeze casting is basically focused on internal factors (such as freezing temperature, freezing method, and slurry composition, etc.), and there are few reports on its external factors (such as applying magnetic fields, electric fields, electromagnetic fields, etc.); in addition, most of them focus on structural materials rather than functional materials. There are no reports on the use of magnetic field freeze casting and infiltration methods to prepare ceramic / paraffin composite materials imitating pearl oysters' "brick-mud structure". Summary of the invention

[0005] In view of the defects existing in the prior art, the present invention provides a pearl oyster-like structural ceramic / paraffin composite phase change energy storage material and a preparation method thereof. Magnetic field freezing casting and pressureless infiltration technology are used to prepare pearl oyster-like "brick-mud" Al2O3 and SiO2 porous ceramics, and the composite phase change energy storage material is obtained after pressureless infiltration of paraffin into the porous ceramics. The composite material has high energy storage density, high thermal conductivity, and controllable microstructure. After the paraffin is melted, it will not leak in the ceramic carrier, and the energy storage efficiency is high and it is environmentally friendly. By imitating the highly ordered "brick-mud" microstructure of pearl oysters to construct a continuous and ordered heat transfer path, the porous ceramic skeleton can achieve high thermal conductivity and anisotropy, which opens up a new way to prepare high-energy storage bionic structural ceramic-based phase change energy storage composite materials.

[0006] 1. The technical solution of the present invention is:

[0007] First, a water-based ceramic slurry containing Fe3O4 is prepared, and then Al2O3 and SiO2 porous ceramics are prepared by magnetic field freeze casting. Subsequently, liquid paraffin is filled into the porous ceramics by pressureless infiltration technology to obtain a ceramic-paraffin composite phase change energy storage material with controllable structure and performance. It has the characteristics of stable shape, high thermal conductivity and energy storage density, and low cost.

[0008] The ceramic powder described in the technical solution includes solid-phase ceramic Al2O3 and SiO2 powder, the particle diameter of the ceramic powder is 0.5-5um, and the magnetic attractant Fe3O4 is 20-500nm, and the content is . The volume fraction of the ceramic powder in the composite material is 10%-30vol%.

[0009] A pearl shell imitation structure ceramic / paraffin composite phase change energy storage material and a preparation method thereof, wherein the steps are as follows:

[0010] (1) Preparation of water-based ceramic slurry:

[0011] The dispersant and the binder are dissolved in a deionized water solution at 50°C respectively, and then mixed with Al2O3, SiO2 ceramic powder and magnetic attractant Fe3O4 powder, wherein the volume percentage of the solid phase ceramic powder in the whole slurry is 10-30%, and the content of the magnetic attractant Fe3O4 in the ceramic powder is 3-10wt% by mass, and the slurry is prepared by ball milling for 10 hours in a planetary ball mill at a speed of 250r / min, and the slurry after ball milling is then vacuum stirred and degassed for 30 minutes at a stirring speed of 80-100r / min to prepare a water-based ceramic slurry;

[0012] (2) Magnetic field freezing casting:

[0013] The magnetic field freezing casting mold is composed of a polytetrafluoroethylene mold, a copper plate and an N35 brand NdFeB strong magnet. Figure 1 As shown. There are polytetrafluoroethylene insulation pads, copper rods, heating coils and thermocouples at the bottom of the a-axis; a rectangular copper plate about 3 mm thick is installed on one side of the b-axis; the magnetic field path is distributed along the c-axis direction from the N pole to the S pole. Pour the water-based ceramic slurry into the magnetic field freezing casting mold, and perform bidirectional freezing at a freezing rate of 3 to 9°C / min. At the same time, during the solidification process of the ice crystals, an external static magnetic field is applied to the mold along the c-axis direction, and the magnetic field intensity is 46 to 138 mT. Due to the directional growth of ice crystals, the ceramic layers will be oriented along the a and b axis directions. At the same time, due to the influence of the magnetic field, the magnetic attractant Fe3O4 is guided by the magnetic field to connect adjacent ceramic layers in the c-axis direction and form a ceramic bridge, and finally obtain the imitation pearl oyster "brick-mud" structure frozen ceramic Al2O3 and SiO2 blanks;

[0014] (3) Freeze drying:

[0015] After demoulding, the frozen ceramic Al2O3 and SiO2 green bodies were quickly placed in a freeze dryer to remove ice crystals by sublimation under vacuum conditions. The freezing temperature was -80°C, the vacuum degree was 10Pa, and the drying time was 48h.

[0016] (4) Sintering of green body:

[0017] The dried ceramic Al2O3 and SiO2 green bodies are sintered at high temperature, heated to 1400°C and 1050°C at 5°C / min, kept at this temperature for 0.5 to 4 hours, and then cooled to room temperature at 5°C / min to obtain porous ceramics with a directional pore structure.

[0018] (5) Pressureless impregnation:

[0019] The sintered Al2O3 and SiO2 blanks are immersed in a paraffin mixed solution at an infiltration temperature of 80-120°C for a time of 5-120 minutes; and dried after treatment.

[0020] The dispersant described in the technical solution includes sodium polymethacrylate; the binder adopts polyvinyl alcohol.

[0021] The frozen ceramic Al2O3 and SiO2 blank with directional distribution described in the technical solution is a rectangular parallelepiped with a length and width of 12 to 20 mm and a height of 15 to 25 mm.

[0022] The process parameters for high-temperature sintering of the ceramic body described in the technical solution are: a heating rate of 4°C / min from 0 to 300°C, keeping warm for 30 minutes at 300°C, a heating rate of 5°C / min from 300 to 900°C, keeping warm for 30 minutes at 900°C, and then continuing to heat to a predetermined temperature of 1050 to 1400°C at a rate of 5°C / min, and keeping warm for 2 to 3 hours.

[0023] 2. Beneficial effects

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The pearl shell imitation structural ceramic / paraffin composite phase change energy storage material and its preparation method described in the present invention adopt a magnetic field freeze casting method to prepare porous ceramics, and its experimental equipment is simple, easy to operate, and environmentally friendly; and the pressureless infiltration technology adopted has lower equipment requirements, simple process, and lower cost compared to pressure infiltration.

[0026] (2) The pearl shell structured ceramic / paraffin composite phase change energy storage material and its preparation method described in the present invention not only adjust the thickness of the ceramic lamellae and the interlamellar spacing by controlling the ceramic content and the freezing speed, but also adjust the density of the ceramic bridges between the lamellae by controlling the magnetic field strength, the magnetic attractant content and other parameters.

[0027] (3) The pearl oyster-like structural ceramic / paraffin composite phase change energy storage material and its preparation method described in the present invention combine the magnetic field freeze casting method and the pressureless infiltration technology. By preparing the complex "brick-mud" structure of the pearl oyster, a continuous and orderly heat transfer path is obtained, thereby improving the thermal conductivity and energy storage performance of the composite phase change material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of magnetic field freeze casting technique;

[0029] Figure 2 Macroscopic morphology of the Al2O3 porous ceramic preform prepared in Example 1;

[0030] Figure 3 Microstructure diagram of the Al2O3 porous ceramic preform prepared in Example 1;

[0031] Figure 4 Microstructure diagram of the Al2O3 ceramic / paraffin composite phase change energy storage material prepared in Example 1;

[0032] Figure 5 Differential scanning calorimetry (DSC) test results of the Al2O3 ceramic / paraffin composite phase change energy storage material prepared in Example 1. DETAILED DESCRIPTION

[0033] Embodiment 1:

[0034] (1) Preparation of water-based ceramic slurry: Sodium polymethacrylate is used as a dispersant and polyvinyl alcohol is used as a binder. They are dissolved in a deionized water solution at 50°C respectively, and then mixed with ceramic (Al2O3) powder with an average particle size of 5 μm. The mixture is ball-milled for 12 h in a planetary ball mill at a speed of 250 r / min to prepare a slurry, wherein the solid-phase ceramic (Al2O3) powder accounts for 10% by volume of the entire slurry, the Fe3O4 content accounts for 3wt% by mass of the ceramic powder, the dispersant content is 1wt% of the mass of the solid-phase ceramic (Al2O3) powder, and the binder content is 1wt% of the mass of the solid-phase ceramic (Al2O3) powder. The ball-milled slurry is vacuum stirred and degassed for 30 min at a stirring speed of 80-100 r / min to prepare a water-based ceramic (Al2O3) slurry.

[0035] (2) Directional solidification: Inject the water-based ceramic (Al2O3) slurry into a polytetrafluoroethylene mold, and perform directionally solidified solidification of the slurry by controlling the cooling temperature (3°C / min) at the upper end of the copper rod. At the same time, during the solidification of the ice crystals, apply an external static magnetic field to the mold along the c-axis direction with a magnetic field intensity of 85mT. During the freezing process, water squeezes the ceramic (Al2O3) particles into the gaps between the ice crystals, forming a directional layered arrangement, and obtaining a frozen ceramic (Al2O3) body with directional ice crystal distribution;

[0036] (3) Freeze drying: After demoulding, the frozen ceramic (Al2O3) green body is quickly placed in a freeze dryer to remove ice crystals by sublimation under vacuum. The freezing temperature is -80°C, the vacuum degree is 10Pa, and the drying time is 48h.

[0037] (4) Sintering of the green body: The dried ceramic (Al2O3) green body is sintered at high temperature to obtain a porous ceramic (Al2O3) with a directional pore structure. The sintering process parameters of the ceramic (Al2O3) green body are: 0-300℃ heating rate is 4℃ / min, keep warm at 300℃ for 30min, 300-900℃ heating rate is 5℃ / min, keep warm at 900℃ for 30min, then continue to heat to 1400℃ at 5℃ / min, keep warm for 2h, and the prepared Al2O3 porous ceramic preform has a macroscopic morphology and microstructure as shown in Figure 2 and Figure 3 As shown;

[0038] (5) Pressureless infiltration: The sintered Al2O3 body is immersed in a paraffin solution at a temperature of 80-120°C for 5-120 min. After treatment, the body is taken out and dried at room temperature to obtain an Al2O3 ceramic / paraffin composite phase change energy storage material. The microstructure of the composite material and its differential scanning calorimetry (DSC) test results are shown in Figures 1 and 2. Figure 4 and 5 Other specific implementation cases and process parameters are shown in Table 1.

[0039] Table 1 Example cases and process parameters

[0040]

[0041]

Claims

1. A method for preparing a shaped ceramic-paraffin composite phase change energy storage material, characterized in that: The specific steps of the method for preparing the shaped ceramic-paraffin composite phase change energy storage material are as follows: (1) Preparation of water-based Al2O3 ceramic slurry: The dispersant and the binder are dissolved in a deionized water solution at 50°C respectively, and then mixed with Al2O3 ceramic powder and magnetic attractant Fe3O4 powder, wherein the volume percentage of the solid phase ceramic powder in the whole slurry is 10-30%, and the content of the magnetic attractant Fe3O4 in the ceramic powder is 3-10wt% by mass, and the slurry is prepared by ball milling for 10 hours in a planetary ball mill at a speed of 250r / min, and the slurry after ball milling is then vacuum stirred and degassed for 30 minutes at a stirring speed of 80-100r / min to prepare a water-based ceramic slurry; (2) Magnetic field freezing casting: The magnetic field freezing casting mold is composed of a polytetrafluoroethylene mold, a copper plate and an N35 brand neodymium iron boron strong magnet; a polytetrafluoroethylene heat insulation pad, a copper rod, a heating ring and a thermocouple are arranged at the bottom of the a-axis; a rectangular copper plate with a thickness of about 3 mm is installed on one side of the b-axis; the magnetic field path is distributed from the N pole to the S pole along the c-axis direction; the water-based ceramic slurry is poured into the magnetic field freezing casting mold and bidirectional freezing is performed at a freezing rate of 3 to 9°C / min; at the same time, during the solidification process of the ice crystals, an external static magnetic field is applied to the mold along the c-axis direction, and the magnetic field strength is 46 to 138 mT; due to the directional growth of the ice crystals, the ceramic layer will be directional and arranged along the a and b-axis directions; at the same time, due to the influence of the magnetic field, the magnetic attractant Fe3O4 is guided by the magnetic field to connect the adjacent ceramic layers in the c-axis direction and form a ceramic bridge, and finally a frozen Al2O3 blank with a "brick-mud" structure imitating pearl oyster is obtained; (3) Freeze drying: After demoulding, the frozen Al2O3 ceramic body was quickly placed in a freeze dryer to remove ice crystals by sublimation under vacuum. The freezing temperature was -80°C, the vacuum degree was 10Pa, and the drying time was 48h. (4) Sintering of green body: The dried ceramic Al2O3 green body is sintered at high temperature, the temperature is raised to 1400°C at 5°C / min, the temperature is kept for 2-3 hours, and then cooled to room temperature at 5°C / min to obtain Al2O3 porous ceramics with directional pore structure; (5) Pressureless impregnation: The sintered Al2O3 porous ceramics are immersed in industrial paraffin melt at an infiltration temperature of 80-120°C for 5-120 minutes. After the infiltration treatment, the ceramics are taken out and cooled at room temperature to obtain an Al2O3-paraffin composite material, wherein the volume fraction of the paraffin is 50-80 vol%.

2. The method for preparing the shaped ceramic-paraffin composite phase change energy storage material according to claim 1, characterized in that: The frozen Al2O3 ceramic blank with the imitation pearl shell "brick-mud" structure is a rectangular parallelepiped, and its length, width and height range is 12 to 25 mm.

3. The method for preparing the shaped ceramic-paraffin composite phase change energy storage material according to claim 1, characterized in that: The process parameters for high-temperature sintering of the Al2O3 ceramic body are: a heating rate of 4°C / min from 0 to 300°C, keeping warm for 30 minutes at 300°C, a heating rate of 5°C / min from 300 to 900°C, keeping warm for 30 minutes at 900°C, and then continuing to heat to a predetermined temperature of 1400°C at a rate of 5°C / min, and keeping warm for 2 to 3 hours.

Citation Information

Patent Citations

  • Preparation method of hot cross-linking type nano paraffin phase-change energy-storage capsule

    CN104645907A

  • A preparation method of heat-crosslinked nano-paraffin phase-change energy storage capsules

    CN104645907B

  • Paraffin / iron tailing ceramic composite phase change energy storage material and melt and infiltration preparation method thereof

    CN107011868A

  • A composite phase change material with PVA as the framework material and its preparation method

    CN110746939B

  • Shell-like nacre layer material with layered structure and preparation method thereof

    CN111574137A

Cited By

  • Bionic Al2O3 porous ceramic with bidirectional gradient structure and preparation method thereof

    CN121063956A